Analysis of a large prostate cancer family identifies novel and recurrent gene fusion events providing evidence for inherited predisposition. Issue 5 (7th January 2022) - Raspin, Kelsie; O'Malley, Dannielle E.; Marthick, James R.; Donovan, Shaun; Malley, Roslyn C.; Banks, Annette; Redwig, Frank; Skala, Marketa; Dickinson, Joanne L; FitzGerald, Liesel M.
Abstract: There is strong interest in the characterisation of gene fusions and their use to enhance clinical practices in prostate cancer (PrCa). Significantly, 50% of prostate tumours harbour a gene fusion. Inherited factors are thought to predispose to these events but, to date, only one study has investigated gene fusions in a familial context. Here, we examined the prevalence and diversity of gene fusions in 14 tumours from a single large PrCa family, PcTas9, using the TruSight® RNA Fusion Panel and Sanger sequencing validation. These fusions were then explored in The Cancer Genome Atlas (TCGA) PrCa data set ( n = 494). Overall, 64.3% of PcTas9 tumours harboured a gene fusion, including known erythroblast transformation‐specific ( ETS ) fusions involving ERG and ETV1, and two novel gene fusions, C19orf48:ETV4 and RYBP:FOXP1 . Although 3′ ETS genes were overexpressed in PcTas9 and TCGA tumour samples, 3′ fusion of FOXP1 did not appear to alter its expression. In addition, PcTas9 fusion carriers were more likely to have lower‐grade disease than noncarriers ( p = 0.02). Likewise, TCGA tumours with high‐grade disease were less likely to harbour fusions ( p = 0.03). Our study further implicates an inherited predisposition to PrCa gene fusion events, which are associated with less aggressive tumours. This knowledge could lead to clinical strategies to predict men at risk for fusion‐positive PrCa and, thus, identify patients who are more or less at risk of aggressive disease and/or responsive to particular therapies.